The role and therapeutic significance of the anoikis pathway in renal clear cell carcinoma - Wang, Jin; Qi, Xiaochen; Wang, Qifei; Wu, Guangzhen (Frontiers in Oncology, 2022)
Anoikis is a specialized mode of programmed cell death. Specifically, once cells detach from the original extracellular matrix, an apoptotic program is initiated, preventing colonization of the cells in distant parts of the organ. Therefore, both distant metastasis and colonization of cancer cells rely on the anoikis resistance of cancer cells. Bioinformatics analysis was performed to confirm the relation of anoikis to kidney renal cell carcinoma (KIRC). To construct a prognostic model for patients with KIRC, we investigated several genes of the anoikis pathway most closely related to KIRC and also contrasted the effects of common anticancer drugs on the KIRC pathway. Besides KIRC, we explored the expression of anoikis-related genes in various other cancers. We classified patients with KIRC into three clusters based on the coefficients and mRNA expression levels of anoikis-related genes selected using the GSVA algorithm. We used the GDSC database to predict the response of the anoikis pathway to common anticancer drugs and explored the potential targets of the anoikis pathway in KIRC. We then analyzed the response of common immunotherapies to the anoikis pathway to analyze the correlation between anoikis and immune checkpoint inhibitor therapy. Finally, eleven cancer-related genes were screened and a prognostic model was constructed using LASSO regression.